THE DANGER OF ASBESTOS AFTER THE BAN OF ITS USE - Перетяка, Сергій (Modern engineering and innovative technologies, 2023)
The paper examines the problem of the danger of asbestos-containing materials in Ukraine after their ban. Asbestos is a truly extraordinary material that has unique properties: corrosion resistance, dielectric, durability, heat resistance, low coefficien